CdZnS-based composite material as well as preparation method and application thereof
Through the coordinated application of amino doping and molybdenum disulfide, the CdZnS-based composite material was constructed, which solved the problems of high photogenerated carrier recombination rate and narrow light absorption range of sulfanzine-zinc-cadmium photocatalysts, and significantly improved its photocatalytic performance and stability.
Patent Information
- Application Number
- CN202510695437.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-28
- Publication Date
- 2025-06-27
AI Technical Summary
The existing sulfhydryl-zinc-cadmium (CdZnS) photocatalysts have defects such as high photogenerated carrier recombination rate and narrow light absorption range in photocatalytic reactions, which limits their practical application.
Through the collaborative application of amino doping and molybdenum disulfide (MoS2) as an electron transport medium, CdZnS-based composites are constructed to improve their specific surface area and photoresponse range.
The photocatalytic performance of CdZnS-based composite materials is significantly improved, the separation and migration efficiency of photogenerated carriers is increased, and the stability and hydrogen production rate of the catalyst are improved.
Smart Images

Figure CN120205211A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of composite materials, and particularly to CdZnS-based composite materials, their preparation methods and applications. Background Art
[0002] Photocatalytic technology uses catalysts to convert solar energy into chemical energy or electrical energy, and has advantages such as environmental protection, sustainability, and low cost. It is widely used in the fields of energy development and environmental pollution control. The performance of the catalyst is the key factor determining the photocatalytic efficiency. Therefore, the design and development of new and efficient catalyst materials have always been the research core in this field. As a metal sulfide catalyst, cadmium zinc sulfide (CdZnS) has received attention in the field of photocatalysis due to its simple preparation process, easy availability of raw materials, and good chemical stability. However, its high recombination rate of photo-generated carriers and narrow light absorption range limit its practical applications.
[0003] To solve the above problems, researchers have tried to optimize the performance of cadmium zinc sulfide through technical means such as element doping, heterostructure construction, and surface modification. For example, noble metal deposition can extend the carrier lifetime, and the construction of composite structures can expand the light response range. However, existing modification methods mostly focus on a single technical path, lack systematic research on the synergistic application of multiple modification means, and the long-term stability of the modified catalyst has not been effectively guaranteed. In addition, the core mechanisms such as the charge transfer path and surface reaction kinetics in the CdZnS photocatalytic reaction have not been fully clarified, resulting in the lack of theoretical guidance for optimization strategies.
[0004] Although certain progress has been made in existing research, the industrial application of CdZnS photocatalytic technology still faces challenges: the compatibility and stability improvement mechanisms of modification methods are not clear, and the lack of understanding of the reaction mechanism restricts the proposal of targeted optimization schemes. Therefore, deeply exploring the photocatalytic reaction mechanism of cadmium zinc sulfide, developing a multi-means synergistic modification strategy and establishing a stability enhancement mechanism have become the key requirements for breaking through its performance bottleneck and promoting practical applications. Summary of the Invention
[0005] Based on this, the present invention provides CdZnS-based composite materials, their preparation methods and applications, which can solve at least one problem in the prior art.
[0006] In a first aspect, the present invention provides a preparation method of a CdZnS-based composite material, which includes the following steps: Mix a soluble zinc salt, a soluble cadmium salt and water to obtain a mixed solution; Add ethylenediamine and thioacetamide to the mixed solution, and carry out a hydrothermal reaction at 175°C - 185°C to obtain amino-doped CdZnS (denoted as N-CZS); Mix the amino-doped CdZnS, molybdenum disulfide (denoted as MS), and organic solvent, and stir vigorously or treat with a cell disruptor to obtain a CdZnS-based composite material (denoted as MS / N-CZS).
[0007] When irradiated with visible light, a photoexcitation effect occurs inside the N-CZS semiconductor material in the CdZnS-based composite material, and photoinduced electrons (e - -) are formed at the conduction band position, and corresponding holes (h + +) are generated in the valence band region. By constructing a heterostructure and introducing MS as an electron transport medium in the CdZnS-based composite material, the electrons in the conduction band of N-CZS can migrate directionally to the surface of MS and then participate in the interfacial reaction of water reduction to produce hydrogen. Thanks to the supporting effect of the MS honeycomb sphere structure, the agglomeration phenomenon of N-CZS is significantly reduced, and the attachment of N-CZS also reduces the agglomeration of MS. This synergistic effect increases the specific surface area of the CdZnS-based composite material and provides sufficient active sites for surface catalytic reactions. Therefore, the CdZnS-based composite material can be used as a catalyst for photocatalytic water splitting to produce hydrogen, and the catalytic effect is good.
[0008] In some alternative embodiments, the molar ratio of zinc in the above soluble zinc salt to cadmium in the soluble cadmium salt is 1:1. Thus, in the amino-doped CdZnS, Cd:Zn = 1:1, which can be denoted as NH2-Cd 0.5 Zn 0.5 S, which helps to improve the catalytic hydrogen production rate of the CdZnS-based composite material.
[0009] In some alternative embodiments, the above soluble zinc salt is zinc acetate, zinc nitrate, zinc chloride, or zinc sulfate, and the above soluble cadmium salt is cadmium acetate, cadmium nitrate, cadmium chloride, or cadmium sulfate. Preferably, the above soluble zinc salt is zinc acetate, and the above soluble cadmium salt is cadmium acetate.
[0010] In some alternative embodiments, the molar ratio of the above thioacetamide to the soluble zinc salt is 2.5:1.
[0011] In some alternative embodiments, the dosage of the above molybdenum disulfide is 8%-12% of the total mass of the above molybdenum disulfide and amino-doped CdZnS. Preferably, the dosage of the above molybdenum disulfide is 10% of the total mass of the above molybdenum disulfide and amino-doped CdZnS.
[0012] In some alternative embodiments, the above organic solvent is ethanol.
[0013] In a second aspect, the present invention provides a CdZnS-based composite material obtained by the preparation method of the above CdZnS-based composite material.
[0014] Thirdly, the present invention provides an application of the above CdZnS-based composite material in photocatalytic water splitting for hydrogen production.
[0015] Fourthly, the present invention provides a catalyst for photocatalytic water splitting for hydrogen production, which comprises the above CdZnS-based composite material.
[0016] Due to the above technical solutions, the embodiments of the present invention have at least the following beneficial effects: Doping amino groups into the CdZnS material, the amino modification effectively improves the photocatalytic performance of the CdZnS-based composite material; the N-CZS particles are anchored on the MS honeycomb spheres, increasing the specific surface area of the CdZnS-based composite material, providing abundant active sites, and the construction of the heterostructure improves the band gap characteristics of the CdZnS-based composite material, expands the light response range, and significantly improves the separation and migration efficiency of photogenerated carriers. Description of the Drawings
[0017] Figure 1 SEM images and TEM images of N-CZS, MS, and 10MS / N-CZS in the embodiments of the present invention.
[0018] Figure 2 EDS elemental mapping images of the 10MS / N-CZS composite material in the embodiments of the present invention.
[0019] Figure 3 XRD spectra of N-CZS, MS, and 10MS / N-CZS in the embodiments of the present invention.
[0020] Figure 4 UV-Vis absorption spectra of CdZnS, N-CZS, MS, and 10MS / N-CZS in the embodiments of the present invention.
[0021] Figure 5 Shows the band gaps of N-CZS and 10MS / N-CZS in the embodiments of the present invention.
[0022] Figure 6 PL spectra of CdZnS, N-CZS, MS, and MS / N-CZS in the embodiments of the present invention.
[0023] Figure 7 Shows the transient photocurrent response test results of CdZnS, N-CZS, MS, and 10MS / N-CZS in the embodiments of the present invention.
[0024] Figure 8 Shows the electrochemical impedance characteristics of CdZnS, N-CZS, MS, and 10MS / N-CZS in the embodiments of the present invention.
[0025] Figure 9Shows the evaluation results of the photocatalytic performance of MS, N-CZS, 8MS / N-CZS, 10MS / N-CZS, and 12MS / N-CZS in the embodiments of the present invention.
[0026] Figure 10 Shows the evaluation results of the cycling performance of 10MS / N-CZS in the embodiments of the present invention. Detailed implementation manners
[0027] The concept of the present invention and the resulting technical effects will be clearly and completely described below to fully elaborate the purpose, solution, and effects of the present invention.
[0028] Example 1 Mix 10 mmol of Zn(Ac)2·2H2O, 10 mmol of Cd(Ac)2·2H2O, and 50 mL of water, and stir for 30 min to obtain a mixed solution; add 10 ml of ethylenediamine (EN) and 25 mmol of thioacetamide (TAA) to the mixed solution, stir again for 30 min, then transfer the uniformly mixed solution to a stainless-steel autoclave equipped with a PTFE liner, and react at a constant temperature of 180 °C for 24 h. After the reaction is completed, cool to room temperature, wash the solid product, and dry to obtain N-CZS; mix 8 mg of MoS2, 92 mg of N-CZS, and 60 mL of ethanol, treat with a cell disruptor at room temperature for 1 h, then stir for 24 h, wash with ethanol and deionized water, and dry in vacuo at 60 °C for 12 h to obtain 8MS / N-CZS.
[0029] Example 2 Mix 10 mmol of Zn(Ac)2·2H2O, 10 mmol of Cd(Ac)2·2H2O, and 50 mL of water, and stir for 30 min to obtain a mixed solution; add 10 ml of ethylenediamine (EN) and 25 mmol of thioacetamide (TAA) to the mixed solution, stir again for 30 min, then transfer the uniformly mixed solution to a stainless-steel autoclave equipped with a PTFE liner, and react at a constant temperature of 180 °C for 24 h. After the reaction is completed, cool to room temperature, wash the solid product, and dry to obtain N-CZS; mix a certain amount of 10 mg of MoS2, 90 mg of N-CZS, and 60 mL of ethanol, treat with a cell disruptor at room temperature for 1 h, then stir for 24 h, wash with ethanol and deionized water, and dry in vacuo at 60 °C for 12 h to obtain 10MS / N-CZS.
[0030] Example 3 10 mmol of Zn(Ac)2·2H2O, 10 mmol of Cd(Ac)2·2H2O and 50 mL of water were mixed and stirred for 30 min to obtain a mixed solution; 10 ml of ethylenediamine (EN) and 25 mmol of thioacetamide (TAA) were added to the mixed solution, and it was stirred again for 30 min. Subsequently, the well-mixed solution was transferred to a stainless-steel autoclave equipped with a polytetrafluoroethylene liner and reacted at a constant temperature of 180 °C for 24 h. After the reaction was completed, it was cooled to room temperature, the solid product was washed and dried to obtain N-CZS; 12 mg of MoS2, 88 mg of N-CZS and 60 mL of ethanol were mixed and treated with a cell disruptor at room temperature for 1 h, then stirred for 24 h and washed with ethanol and deionized water, and vacuum dried at 60 °C for 12 h to obtain 12MS / N-CZS.
[0031] Figure 1 (a) in it is the SEM image of N-CZS. It can be seen that N-CZS presents in the form of spherical nanoparticles. This is because the introduction of amino groups generates a certain repulsive force between the nanoparticles, thus effectively reducing the aggregation phenomenon of the nanoparticles. Figure 1 (b) in it is the SEM image of MS. It can be seen that MS presents a spherical structure with a porous surface, similar to a honeycomb. This characteristic is beneficial to increasing the specific surface area, thereby improving the photocatalytic efficiency of the CdZnS-based composite material, but there is a certain degree of aggregation phenomenon. Figure 1 (c) in it is the SEM image of 10MS / N-CZS. It can be seen that the morphology of this composite material shows that N-CZS nanoparticles are densely distributed on the surface of MS. On the one hand, it makes the N-CZS nanoparticles evenly distributed, and on the other hand, it helps to reduce the aggregation of MS; this uniform distribution helps to maximize the interface area, thereby promoting more effective charge transfer and photocatalytic reaction; the composite structure may further promote the separation of photogenerated electrons and holes through the heterojunction effect, thereby improving the photocatalytic performance. From a structural point of view, the combination of the honeycomb structure of MS and the spherical structure of N-CZS may form an efficient electron transfer path; the MS layer can serve as an electron transport channel, while the N-CZS nanoparticles can serve as light absorption centers; this synergistic effect can significantly improve the overall photocatalytic efficiency of the composite material.
[0032] Figure 1 (d) in it and Figure 1The TEM images of (e) in it are all of 10MS / N-CZS. It can be seen that the circular particles are stacked on each other, which corresponds to the MS honeycomb balls in the SEM image. Since the particle size of the N-CZS nanoparticles is too small to be clearly distinguished in the figure, and no traces of N-CZS nanoparticles are found in other positions, the N-CZS nanoparticles may be tightly attached to the MS honeycomb balls. The N-CZS nanoparticles tightly wrap the MS honeycomb balls, and the two are intertwined and tightly combined, and the MS and N-CZS nanoparticles are uniformly distributed in the composite. It can be seen from Figure 1 in (e) that N-CZS shows a characteristic value of the crystal plane spacing of 0.32 nm, which is highly consistent with the (022) crystal plane parameters in the standard PDF card. The adjacent MS component shows regular lattice fringes of 0.31 nm, and its numerical characteristics match the database records of the (110) crystal plane of MS. It should be noted that the lattice fringes of the two materials show the characteristics of a three-dimensional cross-linked heterostructure, and this staggered arrangement mode effectively constructs a stable heterojunction interface.
[0033] As Figure 2 shown in (g) in it to Figure 2 shown in (k) in it, through the quantitative analysis of the elemental distribution map, it can be seen that the five characteristic elements of Zn, S, Cd, Mo, and N in 10MS / N-CZS show a gradient uniform distribution characteristic in the spatial dimension, confirming that the MS and N-CZS two-phase components have achieved uniform compounding at the molecular level during the hydrothermal synthesis process.
[0034] The X-ray diffraction (XRD) technique was used to analyze the crystal structures of N-CZS, MS, and 10MS / N-CZS. As Figure 3 shown, the XRD characteristic peaks of N-CZS indicate the successful synthesis of the N-CZS solid solution, rather than a simple physical mixture of CdS and ZnS. The peaks of the XRD spectrum of MS at 10.1° and 16.4° correspond to the (110) and (-111) crystal planes of MS respectively. No impurity peaks were detected in the XRD spectra of these two materials, confirming the high purity of the prepared samples. In addition, the characteristic peaks of MS appear on the basis of the N-CZS diffraction peaks in the 10MS / N-CZS composite, preliminarily indicating the successful preparation of the 10MS / N-CZS material.
[0035] Figure 4 The UV-visible absorption spectra of CdZnS, N-CZS, MS, and 10MS / N-CZS are shown. It can be seen that compared with CdZnS, the optical absorption curve of the N-CZS catalyst shows a blue shift phenomenon, and its visible light absorption range is shortened, indicating that the method of embedding functional groups on the surface can adjust the light absorption performance and thus improve the photocatalytic efficiency. 10MS / N-CZS shows a trend of enhanced optical absorption, indicating that the introduction of MS helps to optimize the optical properties of the material.
[0036] As Figure 5 shown, the band gaps of N-CZS and 10MS / N-CZS were measured to be 2.40 eV and 2.30 eV, respectively. The controllable implantation of amino groups can not only regulate the light absorption performance of the material, but also control the band gap of CdZnS. The loading of MS further narrows the band gap of CdZnS, making it easier for electrons to jump to the conduction band.
[0037] Figure 6 shows the PL spectra of CdZnS, N-CZS, MS and MS / N-CZS. It can be clearly seen from the figure that the materials with the PL intensity from high to low are CdZnS, N-CZS and MS / N-CZS in turn. Under visible light excitation, 10MS / N-CZS exhibits a significantly weaker fluorescence emission intensity than other materials. This phenomenon reveals that 10MS / N-CZS has a more efficient photogenerated carrier separation efficiency, and its internal mechanism can be attributed to the optimized electronic band structure that significantly reduces the energy threshold required for electron transition.
[0038] Figure 7 shows the test results of the transient photocurrent response of CdZnS, N-CZS, MS and 10MS / N-CZS. It can be seen that the photocurrent density of 10MS / N-CZS reaches the maximum, which is about 8 times higher than that of N-CZS. This quantitative index strongly proves that the synergistic effect generated by the amino-functionalized modification and the metal sulfide composite can effectively enhance the light capture ability and charge transport kinetics characteristics of the material.
[0039] Figure 8 shows the electrochemical impedance characteristics of CdZnS, N-CZS, MS and 10MS / N-CZS. It can be seen that the materials with the semi-arc diameter from large to small are MS, CdZnS, N-CZS, 10MS / N-CZS in turn. The interfacial charge transfer resistance of 10MS / N-CZS is the lowest. The introduction of surface MS can reduce the charge transfer resistance of N-CZS and improve the transport rate of photogenerated electrons. The photoelectrochemical performance of 10MS / N-CZS is significantly improved, mainly due to the fact that amino doping effectively improves the charge separation efficiency and extends the carrier lifetime, while the introduction of MS further accelerates the charge transport rate.
[0040] Example 4 Prepare 10 mL of an aqueous solution of triethanolamine (TEOA) with a volume fraction of 20%, and then disperse 10 mg of 8MS / N-CZS evenly in this solution. Place it in a quartz reaction device with an effective volume of 50 mL for photocatalytic hydrogen production. Before starting the light irradiation program, the reaction system needs to be degassed in advance by continuously introducing high-purity argon for 20 min to remove the residual air and dissolved oxygen in the system. Select a 300 W xenon lamp as the irradiation source, and set the average light intensity to 35.5 mW / cm 2 , and the light irradiation distance is 20 cm. During the hydrogen production reaction, the reaction system is continuously irradiated for 120 min. After the reaction is completed, use a gas chromatograph equipped with a thermal conductivity detector (TCD) to quantitatively analyze the generated gas. High-purity argon is selected as the carrier gas, and the standard curve method is used to accurately determine the concentration of hydrogen.
[0041] Example 5 Prepare 10 mL of an aqueous solution of triethanolamine (TEOA) with a volume fraction of 20%, and then disperse 10 mg of 10MS / N-CZS evenly in this solution. Place it in a quartz reaction device with an effective volume of 50 mL for photocatalytic hydrogen production. Before starting the light irradiation program, the reaction system needs to be degassed in advance by continuously introducing high-purity argon for 20 min to remove the residual air and dissolved oxygen in the system. Select a 300 W xenon lamp as the irradiation source, and set the average light intensity to 35.5 mW / cm 2 , and the light irradiation distance is 20 cm. During the hydrogen production reaction, the reaction system is continuously irradiated for 120 min. After the reaction is completed, use a gas chromatograph equipped with a thermal conductivity detector (TCD) to quantitatively analyze the generated gas. High-purity argon is selected as the carrier gas, and the standard curve method is used to accurately determine the concentration of hydrogen.
[0042] Example 6 Prepare 10 mL of an aqueous solution of triethanolamine (TEOA) with a volume fraction of 20%, and then disperse 10 mg of 12MS / N-CZS evenly in this solution. Place it in a quartz reaction device with an effective volume of 50 mL for photocatalytic hydrogen production. Before starting the light irradiation program, the reaction system needs to be degassed in advance by continuously introducing high-purity argon for 20 min to remove the residual air and dissolved oxygen in the system. Select a 300 W xenon lamp as the irradiation source, and set the average light intensity to 35.5 mW / cm 2 , and the light irradiation distance is 20 cm. During the hydrogen production reaction, the reaction system is continuously irradiated for 120 min. After the reaction is completed, use a gas chromatograph equipped with a thermal conductivity detector (TCD) to quantitatively analyze the generated gas. High-purity argon is selected as the carrier gas, and the standard curve method is used to accurately determine the concentration of hydrogen.
[0043] Comparative Example 1 Comparative Example 1 is basically the same as Example 4, except that 10 mg of 8MS / N-CZS is replaced with 10 mg of MS.
[0044] Comparative Example 2 Comparative Example 2 is basically the same as Example 4, except that 10 mg of 8MS / N-CZS is replaced with 10 mg of N-CZS.
[0045] Figure 9 The photocatalytic performance evaluation results of MS, N-CZS, 8MS / N-CZS, 10MS / N-CZS, and 12MS / N-CZS are shown. It can be seen that the MS material hardly produces hydrogen, while the hydrogen production rate of the N-CZS material reaches 1593.3 μmol·g -1 ·h -1 , which is a certain degree of improvement compared with the 877.8 μmol·g -1 ·h -1 hydrogen production rate of pure CdZnS. With the gradual increase of the MS content, the photocatalytic activity of MS / N-CZS shows an increasing trend. Among them, the 10MS / N-CZS composite material has the highest photocatalytic hydrogen production rate, reaching 4757.9 μmol·g -1 ·h -1 , which is significantly increased by 3 times compared with pure N-CZS and about 5.42 times compared with pure CdZnS. This significant improvement is mainly attributed to the formation of a unique 10MS / N-CZS heterostructure, which is the result of the strong interaction between the two components. However, when the mass fraction of MS increases to 12%, the hydrogen production rate of 12MS / N-CZS drops to about 4542.5 μmol·g -1 ·h -1 , and the photocatalytic activity decreases, possibly because the excessive MS hinders the light absorption of N-CZS.
[0046] Figure 10 The cyclic performance evaluation results of 10MS / N-CZS are shown. It can be seen that after three consecutive photocatalytic hydrogen production tests, the material can still maintain more than 90% of the initial hydrogen production efficiency. This phenomenon indicates that the performance of 10MS / N-CZS does not show a significant decline, showing good stability and reusability, which is of great significance for the practical application of photocatalytic materials.
[0047] As described above, it is only the preferred embodiment of the present invention. The present invention is not limited to the above embodiments. As long as it achieves the technical effects of the present invention by the same or equivalent means, it should fall within the protection scope of the present invention. Within the protection scope of the present invention, its technical solutions and / or embodiments can have various different modifications and changes.
Claims
1. A preparation method of a CdZnS-based composite material, characterized in that, It includes the following steps: Mix a soluble zinc salt, a soluble cadmium salt and water to obtain a mixed solution; Add ethylenediamine and thioacetamide to the mixed solution, and carry out a hydrothermal reaction at 175 °C - 185 °C to obtain amino-doped CdZnS; Mix the amino-doped CdZnS, molybdenum disulfide and an organic solvent, and stir vigorously or treat with a cell disruptor to obtain a CdZnS-based composite material.
2. The preparation method of the CdZnS-based composite material according to claim 1, wherein The molar ratio of zinc in the soluble zinc salt to cadmium in the soluble cadmium salt is 1:
1.
3. The preparation method of the CdZnS-based composite material according to claim 1, characterized in that, The soluble zinc salt is zinc acetate, zinc nitrate, zinc chloride or zinc sulfate, and the soluble cadmium salt is cadmium acetate, cadmium nitrate, cadmium chloride or cadmium sulfate.
4. The preparation method of the CdZnS-based composite material according to claim 3, characterized in that, The soluble zinc salt is zinc acetate, and the soluble cadmium salt is cadmium acetate.
5. The preparation method of the CdZnS-based composite material according to claim 1, characterized in that, The molar ratio of thioacetamide to the soluble zinc salt is 2.5:
1.
6. The preparation method of the CdZnS-based composite material according to claim 1, characterized in that, The dosage of molybdenum disulfide is 8% - 12% of the total mass of molybdenum disulfide and amino-doped CdZnS.
7. The preparation method of the CdZnS-based composite material according to claim 6, characterized in that, The dosage of molybdenum disulfide is 10% of the total mass of molybdenum disulfide and amino-doped CdZnS.
8. A CdZnS-based composite material, characterized in that, It is obtained by the preparation method of the CdZnS-based composite material according to any one of claims 1 - 7.
9. The application of the CdZnS-based composite material according to claim 8 in photocatalytic water splitting for hydrogen production.
10. A catalyst for photocatalytic water splitting to produce hydrogen, characterized in that, It includes the CdZnS-based composite material according to claim 8.
Citation Information
Patent Citations
Composite photo-catalyst with molybdenum disulfide (MoS2) nanosheet / cadmium sulfide (CdS) nanowire core-shell structure
CN105688945A
Preparation method of porous nano spherical zinc-cadmium sulfide solid solution
CN110102316A
Porous two-dimensional zinc cadmium sulfide nanosheet as well as preparation method and application thereof
CN110975886A
Zinc-cadmium sulfide photocatalyst as well as preparation method and application thereof
CN115228485A
ZnCdS and MoS2 composite photocatalyst as well as preparation method and application thereof
CN116870934A